Highly efficient fluorescent and colorimetric sensing of organic amine vapors based on organometal halide perovskite nanostructures. Issue 25 (14th June 2017) - Wu, Pengcheng; He, Qingguo; Zhu, Defeng; Jiang, Haibo; Jiao, Zinuo; Zhang, Yu; Xu, Wei; Fu, Yanyan; Cao, Huimin; Cheng, Jiangong
Abstract : A simple, highly stable and sensitive fluorescent and colorimetric probe for trace organic amine vapor detection based on CH3 NH3 PbBr3 nanoplates/nanowires. Abstract : Volatile organic amine vapors exist in various areas, which can cause a series of harmful effects on environment and human life. Thus, the detection of organic amine vapors with sensitivity and selectivity is greatly needed. This study reports a simple, low-cost, selective and sensitive fluorescence detection of trace organic amine vapors based on CH3 NH3 PbBr3 (MAPbBr3 ) nanoplates (NPs) and nanowires (NWs). Upon exposure to organic amines vapors, the fluorescence of MAPbBr3 was strikingly and quickly attenuated (<4 s), and the color of MAPbBr3 changed from yellow to white for some of the organic amines (depending on the R group of R-NH x ). This change was rooted in the change of the crystal structure of MAPbBr3 after contacted with different amines. We believe that this result is not only a great advancement in the trace detection of organic amine vapors but is also equally important for fundamental research of organometal halide perovskites.